Bibliometric and Literature Review of Sustainability Research ‎Anchored in The UN SDGs - Kataria, Vibhor; Kaur , Dr. Tavleen; Kaur, Dr. Bhajneet (International Journal of Accounting and Economics Studies, 2025)
Existing literature highlights the exploration of sustainability research anchored in the UN SDGs, examined across different sectors, themes, and ‎geographic boundaries. Understanding the routes through which business practices contribute to sustainable development entails a nuanced ‎review of relevant components across corporate governance structure, stakeholder demands, to societal context. There has been a significant ‎proliferation in scholarly engagement of management and business disciplines with the United Nations Sustainable Development Goals- the ‎UN SDGs. This study adopts a bibliometric analysis using bibliographic coupling to assess the evolving body of knowledge at the intersection of the UN SDGs and business practices. Analysis has been done using R-biblioshiny, VOSviewer, and MS Excel. Drawing on a corpus of 1,133 peer-reviewed articles, indexed in Scopus, between 2015 and 2025. This analysis identifies four dominant thematic clusters: (1) ‎Strategy, framework-based implementation of the UN SDGs by businesses; (2) Emergent themes in sustainability research; (3) Leadership ‎and HRM practices for achieving the implementation of the UN SDGs in the business context; (4) Accounting, Tourism and Human Re-‎source imperatives in the attainment of the UN SDGs. Relying on thematic groups, recognized through literature and bibliographic coupling ‎analysis anchored in UNSDGs. The present research synthesizes existing scholarly studies explaining the UNSDGs integration and execution ‎within businesses. In doing so, the study also outlines purposeful pathways intended for upcoming investigation focused on fostering the ‎organized and inclusive harmonious alignment of sustainability goals in the business and management context‎.
Keywords: Bibliometric Analysis; ESG; Sustainability; SDGs; Scopus; Thematic Review; UN Goals